Non-aqueous electrolytes for sodium-ion batteries. Issue 1 (12th November 2014) - Ponrouch, A.; Monti, D.; Boschin, A.; Steen, B.; Johansson, P.; Palacín, M. R.
Abstract : The first review of the various electrolytes currently used and developed for sodium-ion batteries (SIBs), both in terms of materials and concepts, is presented. Abstract : The first review of the various electrolytes currently used and developed for sodium-ion batteries (SIBs), both in terms of materials and concepts, is presented. In contrast to the Li-ion battery (LIB), which is a mature technology for which a more or less unanimously accepted "standard electrolyte" exists: 1 M LiPF6 in EC/DMC, the electrolyte of choice for SIBs has not yet fully conformed to a standard. This is true for both materials: salts, solvents, or additives, and concept, using the main track of organic solvents or aiming for other concepts. SIB research currently prospers, benefitting from using know-how gained from 30 years of LIB R&D. Here the currently employed electrolytes are emphasized and their effects on practical SIB performance are outlined, scrutinizing the rationale for specific choices made, salts, solvents, additives, concentrations, etc. for each specific cell set-up and usage conditions.